An analysis of efficiency and loan loss provisioning in China’s banking - Xiao, Yuzhen (2017)
This paper examines the loan loss provision behavior and cost efficiency in China commercial banks during the year of 2012 and 2016 for a sample of 101 banks. In the first stage, we gain an x efficiency score from the translog cost function through the Stochastic Frontier Approach, we found an increasing trend of x efficiency score in China during the observed period, and 98% of banks in China are cost efficient. Also, the JSCBs are more efficient than SOCBs while the foreign banks are the most efficient among three. In the second stage, cost efficiency is included in the model to estimate the LLP behavior through the two step system GMM estimator. We support the income smoothing, procyclicality, and capital management behavior in China banks, moreover, we found efficiency is a vital variable to explain the loan loss provision decision.